Choleris Students' Critical Thinking Process In Mathematics Problem Solving - Moh Syukron Maftuh; Nur Fathonah; Ina Nur Roihah (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
The purpose of this study was to describe the critical thinking process of junior high school students with choleric personalities in solving mathematical problems. This research is a descriptive study with a qualitative approach. The subjects in this study were two students of MTs Hasanuddin Sidoarjo class VIII who had choleric personalities obtained from the results of personality tests. The research stages used by the researchers consisted of three stages, namely the preparation stage, the implementation stage, and the analysis stage. The data collection technique in this research is the technique of giving the Mathematical Problem Solving Test (TPMM) and interviews later to obtain valid and credible data, researchers use source triangulation. Based on the results of data analysis, it can be concluded that the choleric subject in solving mathematical problems shows the criteria for critical thinking: focus, reason, inference, situation, clarity, overview at the stage of understanding the problem. At the stage of making a plan for the completion of the choleric subject, it fulfills the criteria for critical thinking, focus, reason, inference, situation, clarity, overview. Likewise, at the stage of implementing the completion plan, the choleric subject meets the criteria for critical thinking, focus, reason, inference, situation, clarity, overview. Meanwhile, at the stage of re-examining the completion plan, the choleric subject only met the criteria for critical thinking, focus, reason, inference, situation, clarity, did not meet the criteria for critical thinking overview. Keywords: Critical Thinking, Mathematical Problem Solving, Choleric Personality